KECERDASAN EKOLOGIS BERBASIS KEARIFAN LOKAL - Hery Susanto; Nadiroh Nadiroh; Rasminto rasminto (PETROGAS: Journal of Energy and Technology, 2023)
Humans play an essential role in other living things, as well as the interests of the environment and nature as a whole. Environmental problems such as flash floods, landslides, droughts, and so on do not only occur in one region or one country, but these environmental problems have become a world problem globally. The human perspective and paradigm in viewing and positioning their environment have led to the current ecological crisis. This study aims to identify and examine environmental preservation efforts. Library research is used by collecting materials that discuss environmental issues and other related sources. The author concludes: humans are equipped with the intelligence to reason through reason, to be able to understand what is in the universe so that humans can manage the earth well to empower natural potential based on its phenomena through empowerment or exploration efforts that are beneficial in various aspects of life. The research results show that a paradigm shift is needed when humans relate to their environment. And, in the aspect of local wisdom, it has taught an environmental ethic, respecting each other and always maintaining ecological balance and harmony.